Echocardiographic Assessment of Cardiac Dysfunction in Patients of Chronic Kidney Disease on Maintenance Hemodialysis - BK, Shyam Kumar; Bassi, S.D.; Sah, Alok Kumar; Acharya, Devendra (Journal of Nepalgunj Medical College, 2019)
Objectives: The Aim of this study to assess and analyze the echocardiographic changes in chronic kidney disease patients on maintenance hemodialysis.Material and methods: We Performed Prospective study of echocardiographic changes in chronic kidney disease (CKD) patients undergoing maintenance hemodialysis at our institute. We performed M-mode echocardiography in 80 CKD patients without obvious clinical evidence of coronary artery disease, Valvular heart disease, congenital heart disease. Data was collected from November 2018 to Nov 2019.Results: 80 Patients Undergoing Hemodialysis were included in our study, out of them Echocardiography finding shown LV dilation and diastolic dysfunction in 39 (48.75%), left ventricular hypertrophy (LVH) in 41 (51.25%), systolic dysfunction and pericardial effusion in 22 (27.5%) and 11 (13.75%) patients respectively. RWMA was present in 10% and Valvular calcification was seen in 5 patients. In sub-group of patients with Hb